Majority versus minority influence: The role of message processing in determining resistance to counter-persuasion - Martin, R; Hewstone, M; Martin, P (2008)
Two experiments examined the extent to which attitudes changed following majority and minority influence are resistant to counter-persuasion. In both experiments participants' attitudes were measured after being exposed to two messages, delayed in time, which argued opposite positions (initial message and counter-message). In the first experiment, attitudes following minority endorsement of the initial message were more resistant to a second counter-message only when the initial message contained strong versus weak arguments. Attitudes changed following majority influence did not resist the second counter-message and returned to their pre-test level. Experiment 2 varied whether memory was warned (i.e., message recipients expected to recall the message) or not, to manipulate message processing. When memory was warned, which should increase message processing, attitudes changed following both majority and minority influence resisted the second counter-message. The results support the view that minority influence instigates systematic processing of its arguments, leading to attitudes that resist counter-persuasion. Attitudes formed following majority influence yield to counter-persuasion unless there is a secondary task that encourages message processing. Copyright © 2007 John Wiley and Sons, Ltd.